The rescue of the use of unconventional food plants: activities in the school of Cerro Branco - RS - Moraes, Rosana Santos de (2020)
Many plants called “bushes”, “innos” or “weeds” make an important economic, ecological, nutritional and medicinal role. These plants or part of them are called Unconventional Food Plants (PANC). Because of the lack of knowledge of these plants by the population, actions are needed to rescue the use of PANC. In this sense, as objectives of the work, it is considered achievement of lectures and tastings of food produced with PANC at the Cerro Branco State College, in Cerro Branco - RS. In addition, at the meeting participants answered questionnaires that sought to investigate previous knowledge about PANC. From the questionnaires it was found that, out of a hundred and thirty-six participants, only nine knew the PANC and that the most recognized and consumed PANC was the blackberry (Morus nigra L.). Regarding the golden rain (Cassia fistula L.), only 40 students know and none consume, showing that there is a need to disseminate information about PANC among the school community, encouraging the consumption of PANC on a daily basis.